TRUK-F DALAM NARASI HUMAN TRAFFICKING - Ignasius Ledot (Jurnal Ledalero, 2014)
Story-telling often conveys a message about a particular problem. The bitter stories of victims as recorded here are just a small part of many such experiences which pierce our conscience, abusing the dignity that is within each one of us. Besides these stories, this essay includes data from victims to remind us that today we face an extremely serious problem in human trafficking. From the cases handled by the Women’s Division of TRUK-F (a faith-based human rights NGO), it is clear that many parties are responsible, commencing with individuals and families, but including government institutions. The problem of human trafficking can befall anyone. TRUK-F has struggled to accompany victims while active in awarenessbuilding campaigning about the problem. The number of cases increases starkly by the day while the bitter stories of the victims, together with the anxiety and restlessness of their families, should invite the concern of everybody to engage in assisting victims while advocating for the ending of this inhuman trade. Kata-kata Kunci: Perdagangan orang, rekrut, korban perempuan, korban anak, pelaku, calo, sindikat, kekerasan, dinas pemerintah, PUB, Polisi, Divisi Perempuan TRUK-F, advokasi, Pastoral Gereja.